Experimental performance evaluation of Profibus-FMS. - Seung Ho Hung
Examines the performance characteristics of the industrial communications network via an experimental model of a manufacturing automation system. In the study presented in this article, an experimental model of a Profibus-based manufacturing automation system was developed. The experimental model consisted of two robots, two conveyor belts, a PLC, an NC machine, and an operator station. Using the experimental model, this study evaluated the delay characteristics of a message transmitted through the fieldbus message specification (FMS) services. FMS is the application layer protocol of Profibus and Foundation Fieldbus. The message delay was measured at each sublayer of the Profibus protocol stack. In this article, after an overview of progress in industrial communication networks and a brief introduction to Profibus and the FMS, the experimental model of the Profibus-based manufacturing automation system developed in this study is presented, and the FMS service delay characteristics obtained from the experimental model are discussed
Keywords: Foundation Fieldbus; NC machine; PLC; Profibus-FMS.; Application layer protocol; Conveyor belts; Delay characteristics; Fieldbus message specification; Industrial communication networks; Industrial communications network; Manufacturing automation system; Message delay; Operator station; Robots